A extensão universitária como lócus da experiência de um vivido - Franciele Fernanda dos Santos Pinto (2024)
The public university is an important space for the production, accumulation and sharing of knowledge. Since the Federal Constitution of 1988, universities have structured their activities considering the inseparability between teaching, research and extension. For the last four years we have been participating in the Web Radio at School extension project, which aims to increase integration between university, school and community, through the construction of web radio programs. It is in the context of this extension project that the central objective of this professional master's research is inserted. We propose to narrate and analyze formative processes experienced by the teacher/researcher when joining the community of teaching practice mediated by participation in the Web Radio at School extension project. To achieve this, we opted for a methodology affiliated with the field of narrative research, within the category of narratives of lived experiences. To construct the data, we went through the teacher/researcher's reflections when narrating her experience within this extension project, from graduation to the beginning of her teaching career. The data were analyzed in light of the theoretical framework of community of practice presented by Lave and Wenger (1991). The results allowed us to better understand the formative perspective of the Web Radio at School extension project, as well as the influence that the experiences throughout the project had on the process of building the teacher/researcher's teaching identity. Furthermore, it allowed us to understand web radio as a social environment, a community of practice, in which learning does not only occur through the sharing of knowledge by coordinators, but through participation and exchange of knowledge between project participants. As an educational resource, we produced a mini-course called “Introduction to the production of Educational Podcast for Web Radio” composed of four workshops that involve familiarization with audio processing software used in podcast production, as well as the languages used in the Podcast, the preparing scripts for recording podcasts and producing web radio programs.